Integrating Artificial Intelligence in Mathematics Education: A Systematic Literature Review on Teachers’ Practices - Kholis, Nur; Sudarman; Andayani , Sutrisni (Research Horizon, 2025)
This study is motivated by the need to improve the quality of mathematics learning in the digital era, where the complexity of subject matter and low student learning motivation require innovative and adaptive approaches. This study aims to analyze the contribution of AI utilization by teachers in improving the mathematics learning process, particularly through the development of technological and pedagogical competencies. The research employs a qualitative approach using a systematic literature review, examining research findings published between 2023 and 2025. The results indicate that continuous training and mentoring play a crucial role in enhancing teachers’ technological literacy, which in turn improves their ability to integrate AI into learning media and instructional modules in a more creative and adaptive manner. The findings also show that AI improves teaching time efficiency, facilitates the identification of students’ learning difficulties, strengthens critical thinking skills, and reduces mathematics anxiety. The implications of this study emphasize that the successful implementation of AI largely depends on teachers’ readiness through sustained digital competence development, enabling AI to function as a catalyst for creating innovative, human-centered, and 21st-century competency-oriented mathematics learning.